Adopting and Imlementation of International Finacial Reporting Standard In Iraq Atheoretical Perspective - et. al., Nawzad Majeed Hamawandy, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Proper adoption of International Financial Reporting Standard (IFRS) has been inextricably linked to global financial market penetration and economic development. Yet most of the developing countries still face some challenges in its adoption. Various studies have examined the benefits and challenges of IFRS adoption. The organization and culture, resistance to change, knowledge of IFRS and government policy has dominated the discourse on the challenges of IFRS adoption in developing countries. As we consider the shift in discourse towards the developing countries, this paper explore the empirical analysis studies that analyzing the challenges hindering the proper adoption of IFRS, and its implication for financial market development and economic growth. This paper develops the main issues that pose a challenge to IFRS adoption in developing country like Iraq by reviewing the existing empirical evidence in the literature